Factors Associated with Delayed Diagnosis of Cervical Cancer in Tikur Anbesa Specialized Hospital, Ethiopia, 2019: Cross-Sectional Study - Zeleke, Shegaw (Cancer Manag Res, 2021)
BACKGROUND: Cervical cancer is a preventable and curable disease if detected early enough. But several numbers of women in Ethiopia strive for treatment when the disease has extended to the last stage. Delay in diagnosis is the main reason for cervical cancer mortality in Ethiopia. The main objective of this study was to assess factors associated with delayed diagnoses of cervical cancer in Tikur Anbesa Specialized Hospital, Ethiopia. METHODS: An institution-based cross-sectional study was conducted. Randomly selected 422 cervical cancer patients were interviewed and their medical records were reviewed. Data were entered using EpiData version 3.1 and analyzed using SPSS version 22. Bivariate and multivariate analyses were conducted to examine the association between independent and outcome variables. RESULTS: A total of 410 women participated in the study with a response rate of 97.1%. The mean age of the women was 50 years (SD ±11.5). Half of the participants cannot read and write, and 66.3% of participants' income was <500 Ethiopian Birr (approximately 14 USD). Around 86.3% of the women had delayed diagnosis of cervical cancer. Women who have <500 Ethiopian Birr (14 USD) income (adjusted OR=3.79, CI: 1.48, 9.67), have no awareness of cervical cancer disease (adjusted OR=1.33, CI: 1.05, 2.71) and have no awareness about cervical cancer screening (adjusted OR=1.64, CI: 1.16, 4.07) were more likely for delayed diagnosis of cervical cancer. CONCLUSION: Our study reports a high prevalence of delayed diagnosis of women with cervical cancer. A high level of illiteracy, low socioeconomic status, lack of awareness, traditional healers and absence of a routine screening program were accountable for delayed diagnosis of cervical cancer. Regular cervical cancer screening and expansion, raising awareness, increasing access and improving health services for cervical cancer patients should be promoted and advocated to decrease the usual delay in cervical cancer diagnosis.